Artificial Intelligence for Human Resource Management: A Comprehensive Review - Singh, Priti (Brixton Scholarly Review, 2025)
Artificial Intelligence (AI) is revolutionizing the landscape of human resource management (HRM), offering advanced tool and techniques to streamline processes, enhance decision-making and improve employee satisfaction. The concept of artificial intelligence is still disputed and experts are currently debating on its usefulness for humans. It is the most debated technology which has taken control over various functions. The purpose of this paper is to research the implications that technological advancements, in particular Artificial Intelligence (AI), have for the recruitment process. It aims to investigate where AI can be implemented in the traditional recruitment process and possibly make the process more effective, as well as what the implications would be of having AI within recruitment. This paper searches the role of AI in HR practices. This study examines the integration of AI in HRM. This paper uses a qualitative study the paper is based on secondary data, including scholarly articles, industry reports and case studies. At the end the findings reveal that AI applications in recruitment, performance appraisal, employee engagement and training significantly enhance efficiency and objectivity. The most suitable parts to implement AI in traditional recruitment include recruitment activities such as pre-selection and communication with candidates and sending out recruitment results for applicants. However, challenges such as data privacy, ethical considerations and the potential for workforce displacement remain critical concerns. By synthesizing existing research, this article highlights the dual impact of AI- its potential to drive innovation in HRM while necessitation robust frameworks to address associated risk. The study underscores the need for HR professionals to balance technological advancements with a human – centric approach, ensuring that AI complements rather than replaces traditional HR practices. This analysis serves as a foundation for future research and practical implementation in the evolving domain of HRM.